UPAYA MENINGKATKAN LATIHAN PULL UP TERHADAP KEMAMPUAN POWER PUKULAN LURUS DI DALAM PENCAK SILAT PADA SISWA EKSTRAKURIKULER DI SMK 2 MUHAMMADIYAH KUNINGAN - Hamzah Rifai Hamzah (STKIP Muhammadiyah Kuningan, 2023)
EFFORTS TO IMPROVE PULL UP EXERCISE TOWARDS POWER ABILITY IN PENCAK SILAT IN EXTRACURRICULAR STUDENTS OF SMK 2 MUHAMMADIYAH KUNINGAN, Physical Education, Health and Recreation (PJKR), 2018. In learning pencak silat, it focuses on the type of pull-up exercise on the power ability of straight strokes. The method in this research is the experimental method. With a sample of 15 people, the design used was a pretest-posttest one group design. The difference between the average pretest and posttest shows a significant change from the pull up exercise, where the average pretest result is 17.50 while the average posttest value is 23.83. Data analysis technique using t test. The results of the study obtained the results of the calculation of the Paired Sample T-Test which showed that the value of Sig. (2-tailed) in Pairs 1 and 2 of 0.000 < 0.05, this indicates a significant effect of pull up exercises on the ability to strike straight in pencak silat in extracurricular students at SMK 2 Muhammadiyah Kuningan.